Study of Thermoelectric Generator Utilization to Recover Heat at Low Temperature Grade Application: A Review - Rihardian Maulana Wicaksono; Putty Yunesti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
Generally, the supply of heat energy is abundant in this world especially from direct solar radiation or combustion process activity. However, this energy is mostly wasted and discharged to the environment without recovery and re-utilization process. There is a potential utilization this heat to be converted to electricity using thermoelectric generator (TEGs). This technology device has an ability to convert heat to electricity by difference temperature from both surfaces. This device could prevent thermal loss to environment and optimize the system to generate electricity for small and micro scale power generation. This research conducts a literature review about identifying several potential object application or equipment as heat sources from solar energy or combustion activity combine with thermoelectric generator at low grade temperature that has been worked by previous researcher for past 5 years. Current status and working principal of thermoelectric generator is presented briefly. Several parameters such as working temperature range, potential output power, and efficiency system are described and presented. Then, some implementation challenge and opportunity development combination TEGs with each object applications are discussed and analyzed to produce recommendation for further research